2013
DOI: 10.1371/journal.pone.0058488
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Restraint Stress Increases IL-6, Reduces IL-10, and Causes Persistent Depressive-Like Behavior That Is Reversed by Recombinant IL-10

Abstract: Altered inflammatory cytokine profiles are often observed in individuals suffering from major depression. Recent clinical work reports on elevated IL-6 and decreased IL-10 in depression. Elevated IL-6 has served as a consistent biomarker of depression and IL-10 is proposed to influence depressive behavior through its ability to counterbalance pro-inflammatory cytokine expression. Clinical and animal studies suggest a role for IL-10 in modifying depressive behavior. Murine restraint stress (RST) is regularly em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
135
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(148 citation statements)
references
References 86 publications
11
135
0
2
Order By: Relevance
“…Previous work from our lab and others has shown increased social avoidance (a behavior associated with affect and mood) following social defeat in mice [41,42]. Here, we have shown that RSD-induced enhancement in social avoidance is maintained even 28 days after stress, and that this maintenance temporally corresponds with reduced number of neurons in the caudal hippocampus.…”
Section: Discussionsupporting
confidence: 68%
“…Previous work from our lab and others has shown increased social avoidance (a behavior associated with affect and mood) following social defeat in mice [41,42]. Here, we have shown that RSD-induced enhancement in social avoidance is maintained even 28 days after stress, and that this maintenance temporally corresponds with reduced number of neurons in the caudal hippocampus.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, several lines of evidence indicate that both acute and chronic stress lead to increase in serum pro-inflammatory cytokine levels in animal studies with unclear mechanisms. 24,25) Interestingly, Voorhees et al also found that IL-10 has been decreased following a stress paradigm, indicating that stress may not only alter the pro-inflammatory cytokines but also the antiinflammatory cytokines. It should be mentioned that pro-inflammatory cytokines may activate the HPA axis directly to augment the stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research indicated that the dysregulation of pro-and anti-inflammatory cytokines have a crucial role in the pathophysiology of depression [38] . Pro-inflammatory cytokines (TNF-α, IL-1ÎČ) or lipopolysaccharide-induced depressive-like behavior and neuroinflammatory reaction can be reversed by anti-inflammatory cytokines, such as TGF-ÎČ and IL-10 [39,40] . Conversely, anti-inflammatory agents have therapeutic benefits for mood disorders [41,42] .…”
Section: Discussionmentioning
confidence: 99%